Does Outward Foreign Direct Investment affect domestic real wages? An investigation using French micro-data - Alexandre Gazaniol; Catherine Laffineur (FIW - Research Centre International Economics, 2015)
This paper investigates to which extent outward foreign direct investment (FDI) affects domestic wages. We are first interested in the raw wage differential between multinational and domestic firms. Results reveal that multinational companies pay a wage premium to their employees, even within precise skill-groups (blue-collar workers, intermediate occupations and managers). The wage premium is increasing within the wage distribution. In a second step, we use spell of workers within a firm in a fixed effect model to analyze the effect of outward FDI within job-spells. Results suggest that outward FDI raises wages for managers and reduces wages for workers performing offshorable tasks. The positive effect of FDI on managers' wages is mainly driven by the intensive margin of outward FDI, that is by large firms already established abroad. This result is observed even after controlling for endogenous workers' mobility.
Keywords: J24; J31; D21; D23; 330; Offshoring; Tasks; Wages; Inequality